Impact of foreign direct investment inflows on labour productivity in Nigeria - Uzoma Mirian, Anyachebelu; Ezenekwe, Uju Regina Ezenekwe; Anyanwu, Uchenna (Journal of Management and Economics Innovation, 2025)
This study focused on the impact of foreign direct investment inflows on labour productivity in Nigeria. It specifies an Autoregressive Distributed Lag (ARDL) model, following the work of Hailat and Baniata (2018), to evaluate the impact of international capital inflows—Foreign Direct Investment (FDI), Foreign Portfolio Investment (FPI), Official Development Assistance (ODA), and External Debt (ED)—on labour productivity in Nigeria. The ARDL bounds test is used to determine the existence of cointegration among variables, while the Error Correction Model (ECM) captures both short-run and long-run dynamics. Finally, the Fully Modified Ordinary Least Squares (FMOLS) method is employed to validate the robustness of the estimates. The Akaike Information Criterion (AIC) guided lag selection for the Autoregressive Distributed Lag (ARDL) model, with maximum lags of (1) and (2) chosen via E-Views 10. Results show that Foreign Direct Investment (FDI) negatively affects labour productivity (−0.0074, p=0.0002), while Foreign Portfolio Investment (FPI) and Official Development Assistance (ODA) are insignificant. External Debt (ED) has a negative significant effect (−0.0164, p<0.05). Personal Remittances (PRER) and Real Gross Domestic Product (RGDP) positively influence productivity (0.0046, p<0.05; 1.0931, p<0.01), while Gross Fixed Capital Formation (GFCF) shows a strong negative link (−0.3862, p<0.01). Secondary School Enrollment Rate (SERR) remains positive (0.002, p<0.05). The study concludes that sustainable labour productivity growth in Nigeria requires policies that strengthen domestic absorptive capacity, improve institutional quality, and channel foreign capital toward skill development and technology-driven sectors